2004
DOI: 10.1111/j.1365-3059.2004.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Spread of Sugarcane yellow leaf virus in sugarcane plants and fields on the island of Réunion

Abstract: The spread of Sugarcane yellow leaf virus (SCYLV) in sugarcane plants was studied on Réunion using virus-infected cuttings from four cultivars (R570, R575, R577 and R579). One month after the germination of cuttings in an insect-proof glasshouse, SCYLV was detected by reverse-transcription polymerase chain reaction (RT-PCR) and tissue-blot immunoassay (TBIA) in the leaves, shoots and roots of all cultivars. The distribution of SCYLV in the whole plant did not vary over a 10-to 11-month period of growth. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 15 publications
4
48
0
2
Order By: Relevance
“…Screening of SCYLV in Hawaii revealed positive infection in all susceptible sugarcane cultivars but disease symptoms appeared only occasionally [14]. However, this nonsymptomatic stage can still lead to significant (20-30 %) yield decline [15]. These studies clearly indicated that nonsymptomatic plants still harbour very high titre for SCYLV.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Screening of SCYLV in Hawaii revealed positive infection in all susceptible sugarcane cultivars but disease symptoms appeared only occasionally [14]. However, this nonsymptomatic stage can still lead to significant (20-30 %) yield decline [15]. These studies clearly indicated that nonsymptomatic plants still harbour very high titre for SCYLV.…”
Section: Discussionmentioning
confidence: 62%
“…Also, they found about 25 % of the plants within a plot were asymptomatic. Screening of SCYLV in Hawaii revealed positive infection in all susceptible sugarcane cultivars but disease symptoms appeared only occasionally [14]. However, this nonsymptomatic stage can still lead to significant (20-30 %) yield decline [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations